1980
DOI: 10.2172/5325623
|View full text |Cite
|
Sign up to set email alerts
|

Status report on LWR spent fuel IAEA leach tests

Abstract: Spent light-water-reactor (LWR) fuel with an average burnup of 28,000 MWd/ MTU was leach-tested at 25°C using a modified version of the International Atomic Energy Agency (IAEA) procedure. Leach rates were determined from tests conducted in five different solutions: deionized water, sodium chloride (NaCl), sodium bicarbonate (NaHC0 3), calcium chloride (CaC1 2) and Waste Isolation Pilot Plant (WIPP) "B" brine solutions. Elemental leach rates are reported based on the release of 90Sr + 90y, 106Ru , 137Cs , 144C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 8 publications
(9 reference statements)
2
21
0
Order By: Relevance
“…I u 5c5 (3) 5D5 (3) 3B5A (3) 3B5B (11) 243 ( a ) Number i n parentheses i n d i c a t e s t h e number o f whole p e l l e t s b e f o r e s i z e a n a l y s i s . P a r t i c l e s i z e s were a l s o obtained by Katayama, Bradley and Harvey (1980) f o r H. 6 . Robinson I 1 spent f u e l t h a t reached a burnup o f 28 MWd/kgM.…”
Section: P a R T I C L E P H Y S I C A L C O N D I T I O N A F T E R mentioning
confidence: 99%
See 2 more Smart Citations
“…I u 5c5 (3) 5D5 (3) 3B5A (3) 3B5B (11) 243 ( a ) Number i n parentheses i n d i c a t e s t h e number o f whole p e l l e t s b e f o r e s i z e a n a l y s i s . P a r t i c l e s i z e s were a l s o obtained by Katayama, Bradley and Harvey (1980) f o r H. 6 . Robinson I 1 spent f u e l t h a t reached a burnup o f 28 MWd/kgM.…”
Section: P a R T I C L E P H Y S I C A L C O N D I T I O N A F T E R mentioning
confidence: 99%
“…Microprobe Measured X-Ray I n t e n s i t i e s f o r Cesium, Z i r c o n i um, and I o d i n e (Katayama, Bradley and Harvey 1980) g r a d i e n t f r o m edge t o c e n t e r , w i t h a 47% r e d u c t i o n i n t h e x-ray i n t e n s i t y , 300 pm inward from t h e f u e l surface, and an a d d i t i o n a l 28% drop over t h e n e x t 3600 pm t o t h e f u e l c e n t e r . Technetium, barium, cerium, and cesium were s l i g h t l y e n r i c h e d a t t h e f u e l surface.…”
Section: Gplsmentioning
confidence: 99%
See 1 more Smart Citation
“…This might explain why he saw very low solution concentrations of uranium in deionized water, an observation that is in agreement with the "true solution" concentration of uranium obtained in the NNWSI Project deionized water studies (Wilson, 1985a) after subtraction of the particulate component. Katayama et al (1980) reported results of the leaching of H. B. Robinson spent fuel in deionized water, 0.03M NaHCOj, -nd three other leachants. They used the same general test procedure as did Johnson (1982), but used bare fuel fragments 2 to 5 mm in size, 15 gof fuel, and 300 mL of soh'ticn.…”
Section: Fine Fuel Particle From Hb Robinson/ J-13 Bare Fuel Test 2mentioning
confidence: 99%
“…In the future, it would be desirable to report the complete set of experimental data in a manner that allows others to evaluate the significance of the various components. Katayama et al (1980) also reported data for sodium bicarbonate water leaching. The bicarbonate concentration was approximately 1800 ppm, a level much higher than any of the groundwaters used in NNWSI, SKB/KBS, or Canadian fuel leaching.…”
Section: Fine Fuel Particle From Hb Robinson/ J-13 Bare Fuel Test 2mentioning
confidence: 99%